2016
DOI: 10.1136/bcr-2016-215220
|View full text |Cite
|
Sign up to set email alerts
|

Von Meyenburg complex and complete ductal plate malformation along with Klatskin tumour: a rare association

Abstract: Von Meyenburg complexes (VMCs), or bile duct microhamartomas, are among the constellation of defects of ductal plate malformation. These present as multiple small intrahepatic cysts and are diagnosed incidentally. Association of intrahepatic VMCs with a bile duct cancer has rarely been reported. We describe a case of a 53-year-old man presenting with obstructive jaundice. Biochemistry and radiology gave a provisional diagnosis of a resectable Klatskin tumour. The patient underwent right hepatectomy with common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Ommental caking, presence of generalized lymphadenopathy with GI involvement favours TB. The overlap of the signs is further complicated by the fact that certain hepatic plate dysgenesis like von meyenburg complexes [20] may be seen in patients of benign diseases producing a mirage of malignant pathology. Furthermore, there have been reports of multiple peritoneal nodules seen on diagnostic laparoscopy which regressed after antitubercular treatment [21].…”
Section: Differentiation Of Benign and Malignant Massesmentioning
confidence: 99%
“…Ommental caking, presence of generalized lymphadenopathy with GI involvement favours TB. The overlap of the signs is further complicated by the fact that certain hepatic plate dysgenesis like von meyenburg complexes [20] may be seen in patients of benign diseases producing a mirage of malignant pathology. Furthermore, there have been reports of multiple peritoneal nodules seen on diagnostic laparoscopy which regressed after antitubercular treatment [21].…”
Section: Differentiation Of Benign and Malignant Massesmentioning
confidence: 99%
“…In the past, when the diagnosis of BDH relied on pathological examination following liver biopsy, it was considered to be a benign disease, managed by regular observation rather than surgery. However, in recent years, an increasing number of cases demonstrated that there is a possible association between BDH and intrahepatic cholangiocarcinoma (3)(4)(5). Therefore, BDH should be resected when possible.…”
Section: Introductionmentioning
confidence: 99%